Perceptions of the brazilian obstetrics physicians about the term obstetric violence: A cross-sectional study - Terribile, Diogo Coutinho; Filho, Carlos Izaias Sartorao [UNESP] (FapUNIFESP (SciELO), 2023)
INTRODUCTION: We observe a growing global discussion about the practices considered obstetric violence against women during pregnancy and childbirth. Otherwise, the indiscriminate subjective and lay interpretation of the term obstetric violence can lead to a misunderstanding among medical professionals. OBJECTIVE: This study aimed to describe the obstetrician s perceptions about the term obstetric violence and the medical groups affected negatively by the topic. METHODS: A cross-sectional study applied to Brazilian obstetrics physicians regarding their perceptions of obstetric violence. RESULTS: From January to April 2022, we sent about 14,000 direct mail nationwide. A total of 506 participants responded. We observed that 374 (73.9%) participants consider the term obstetric violence nocive or harmful to professional practice. Furthermore, after Poisson regression, we described that the respondents who graduated before 2000 and from a private institution were significant and independent groups for the full or partial agreement that the term is nocive for the obstetricians in Brazil. CONCLUSION: We observed that almost three in four obstetrician participants consider the term obstetric violence nocive or harmful to professional practice, particularly in those who graduated before 2000 and from a private institution. The findings are relevant to propose further debates and strategies to mitigate the possible harms caused to the obstetrician team by the indiscriminate use of the term obstetric violence.
Keywords: Gender-based violence; Obstetrics; Parturition; Physician-patient relations; Pregnancy; Professional-patient relations